HEMA-free versus HEMA-containing adhesive systems: a systematic review - Esraa Abdelkhalek; Hamdi H. Hamama; Salah H. Mahmoud (Systematic Reviews)
Abstract Background Hydrophilic monomer 2-hydroxyethyl methacrylate (HEMA)-free adhesive systems are gaining increasing popularity nowadays. Although the addition of HEMA to dental adhesives improves dentin wettability and resin diffusion into demineralized collagen fibrils, HEMA’s high hydrophilicity can lead to hydrolytic degradation of the adhesive interface. Thus, HEMA-free adhesive systems have been developed. Unfortunately, the lack of HEMA in the adhesive composition may lead to a separation phase between hydrophobic and hydrophilic components. The aim of this systematic review was to evaluate the clinical performance of HEMA-free adhesive systems and compare them with HEMA-containing ones. Methods An electronic search of The National Library of Medicine (MEDLINE/PubMed) was conducted. Eligibility criteria were reporting empirical data from clinical studies published between 2013 and 2023 about the clinical performance of HEMA-free adhesive systems for direct resin composite restorations. Studies with at least 2-year clinical follow-up done in permanent dentition in any form of cavities were selected. The included studies were assessed for risk of bias using the modified Cochrane Collaboration tool criteria. Results The database search returned 147 studies; a total of 7 studies were included in this review; the majority of studies reported no significant difference between the two types of adhesives for the parameter of retention. Conclusions HEMA-free adhesive systems exhibited good clinical performance with regard to retention. There was some concern about their influence on marginal adaptation and marginal discoloration due to the conflicted results reported by the included trials. Thus, the results need to be confirmed with long-term evaluations. Systematic review registration PROSPERO CRD42023448952.